The socio-spatial segregation in two costal tourist cities: Acapulco and Cancún (2019)
The objective of this work is to analyze two coastal tourist cities: Acapulco and Cancún as cities that are configured socio-spatially in a segregated manner. This study is developed through the territorialization of statistical data. First, the different historical urbanization processes of both metropolitan areas are defined, under the recognition of how the tourism dynamics are structured, valued and defined in each one of them. Secondly, the relationship established among the configuration of the tourist area, the social indexes, the equipment and the housing density is analyzed. Finally, the idea that tourism generates complex processes with multiple territorial effects, involving functional specializations, is discussed, which in turn reinforces an increase in socio-spatial segregation by isolation of hotel and housing areas and trends in the development of the commercial nodes and tertiary corridors.